Gender and the digital economy perspectives from the developing world - Mitter, Swasti, 1939-2016.; Ng, Cecilia, 1950-; Sage eBooks (New Delhi ; London : SAGE, 2005)
Ng (Asian Institute of Technology, Thailand) and Mitter (an international consultant on information and communication technologies who has worked for the United Nations and the World Bank) have selected nine articles from issues of the journal Gender, Technology and Development (based out of the Gender and Development Field of Study).
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Information society -- Developing countries; Information technology -- Economic aspects -- Developing countries; Women in economic development -- Developing countries; Women -- Effect of technological innovations on -- Developing countries; Women -- Developing countries -- Economic conditions -- 21st century; Electronic books